Predicting urban design effects on physical activity and public health: A case study. (September 2015) - MacDonald Gibson, Jacqueline; Rodriguez, Daniel; Dennerlein, Taylor; Mead, Jill; Hasch, Trisha; Meacci, Grant; Levin, Stuart
Abstract: With increasing global concerns about obesity and related health effects, tools to predict how urban form affects population physical activity and health are needed. However, such tools have not been well established. This article develops a computer simulation model for forecasting the health effects of urban features that promote walking. The article demonstrates the model using a proposed small-area plan for a neighborhood of 10, 400 residents in Raleigh, North Carolina, one of the fastest-growing and most sprawling U.S. cities. The simulation model predicts that the plan would increase average daily time spent walking for transportation by 17 min. As a result, annual deaths from all causes are predicted to decrease by 5.5%. Annual new cases of diabetes, coronary heart disease, stroke, and hypertension are predicted to decline by 1.9%, 2.3%, 1.3%, and 1.6%, respectively. The present value of these health benefits is 21, 000 per resident.